Pemasangan Kata-Kata Unik menggunakan Kayu Bekas Guna Meningkatkan Potensi Wisata Lembah Winden - Yudhoyono, Aryo Prasetyo; Baihaqi, Aufa Izzudin (Jurnal Bisnis Indonesia, 2024)
Tourism development using used materials is a very good thing to do for the purpose of developingtheir tourism as well as processing non-value materials into valuable ones. This can be the first stepto increase the existing tourism potentials, by using used wood to make a tourist decoration as well asa photo spot for visitors. The method used is a discussion and direct survey to the Winden Valley tour,and the practice of making these words using paint and used wood provided by Wonosalam residents.This activity not only increases tourism potential but also reduces existing wastes by reprocessingthem, which in the end the Winden Valley accepts these unique words.Keywords: Tourism Development; Used Materials; Tourism Potential